Making Work Pay in Nicaragua : Employment, Growth, and Poverty Reduction - Gutierrez, Catalina (Washington, DC : World Bank, 2012)
The objective of this report is to provide some policy guidelines for the fight against poverty. In particular, it hopes to be able to identify the growing sectors, as well as the constraints faced by the poor in benefiting from this growth. The report is part of a series of studies conducted within the Poverty Reduction Group (PRMPR) to foster understanding of the role of employment earnings and labor markets in shared growth. In addition, it is intended to function as a background document for the World Bank's Nicaragua Poverty Assessment 2007. The degree to which growth is able to translate into poverty reduction depends on how its benefits are distributed among different segments of society. There is little doubt that growth measured by changes in average income contributes significantly to poverty reduction. However, it is also clear that countries differ in the degree to which income growth spells have translated into poverty reduction. Although differences in the responsiveness of poverty to income growth account for a small fraction of the overall differences in poverty changes across countries, from the point of view of an individual country, these differences may have significant implications for poverty reduction, especially in the short term.